Analyzing and addressing false interactions during compiler optimization phase ordering. (22nd January 2013) - Jantz, Michael R.; Kulkarni, Prasad A.
SUMMARY Compiler optimization phase ordering is a fundamental, pervasive, and long‐standing problem for optimizing compilers. This problem is caused by interacting optimization phases producing different codes when applied in different orders. Producing the best phase ordering code is very important in performance‐oriented and cost‐constrained domains, such as embedded systems. In this work, we analyze the causes of the phase ordering problem in our compiler, Very Portable Optimizer (VPO), and report our observations. We devise new techniques to eliminate, what we call, false phase interactions in our compiler. We find that reducing such false phase interactions significantly prunes the phase order search space. We also develop and study algorithms to find the best average performance that can be delivered by a single phase sequence over our benchmark set and discuss the challenges in resolving this important problem. Our results show that there is no single sequence in VPO that can achieve the optimal phase ordering performance across all functions. Copyright © 2013 John Wiley & Sons, Ltd.